2018
DOI: 10.1002/aocs.12096
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Candelilla Wax, Monoacylglycerols, and Fully Hydrogenated Oil Oleogels

Abstract: Oleogels have been studied in the past decade due to their potential to replace saturated fat in foods. Oleogelators have been mostly studied alone or in binary systems. Sometimes a single oleogelator cannot achieve all the technological properties necessary for a specific food application. Thus, the aim of this work was to investigate the interaction between candelilla wax (CLX), monoacylglycerols (MAG), and a fully hydrogenated oil (hardfat [HF]) in soybean and high‐oleic sunflower oils and to evaluate their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 31 publications
4
47
1
3
Order By: Relevance
“…Each oleogelator (CLX, MAG, and HF) was added in the same proportion (2%). Previous experiments in our laboratory have shown that these concentrations of oleogelators result in good oil entrapment but in low hardness (da Silva et al, ). Therefore, these same oleogelators were chosen to test if sonication could improve the hardness of the oleogel.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Each oleogelator (CLX, MAG, and HF) was added in the same proportion (2%). Previous experiments in our laboratory have shown that these concentrations of oleogelators result in good oil entrapment but in low hardness (da Silva et al, ). Therefore, these same oleogelators were chosen to test if sonication could improve the hardness of the oleogel.…”
Section: Methodsmentioning
confidence: 90%
“…The addition of water to form the EG reduced D m ( P < 0.05) and additionally changed the crystal morphology of the samples (EG5 and EG25) in relation to the EG0. Before water addition, spherulite‐shaped crystals were observed but only small needles were observed after water addition (da Silva et al, ). HIU decreased crystal sizes in sample EG0 ( P < 0.05), but did not change the crystals for samples with water addition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OL and OM are two important methods used to describe the ability of the crystalline network to retain oil (da Pieve et al., 2010; da Silva & Martini, 2019; da Silva et al., 2018, 2019; Jahaniaval, Kakuda, & Abraham, 2002; Kanagaratnam, Enamul Hoque, Mat Sahri, & Spowage, 2013; Maleky, Mccarthy, Mccarthy, & Marangoni, 2012; Marty & Marangoni, 2009). Although both methods measure basically the same thing (ability to retain oil), the mechanism by which the oil is released from the crystalline matrix is not the same.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of oil that migrated out of the crystalline matrix was quantified by measuring the diameter of the stain of oil on the filter paper expressed in cm. Three different cylinders were prepared for each crystallization condition (da Silva, Arellano, & Martini, 2018). The crystalline material left on the top of the filter paper after the OM experiment was used to evaluate differences in the crystalline material after OM.…”
Section: Methodsmentioning
confidence: 99%